Interrupted mattress versus continuous subcuticular versus stapler: a comparative study on wound closure outcomes in primary caesarean section with Pfannenstiel incision - Chaurasia, Amrita; Jain, Kajal; Ojha, Vandana; Sachan, Nidhi; Singh, Vidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of the study was to compare the suture techniques using interrupted mattress and continuous subcuticular and stapler in terms of wound closure time; pain in stitch line on post-operative day 3, 5 and 7 and patient satisfaction. Methods: All patients fulfilling the inclusion criteria, were divided into 3 categories (interrupted mattress, subcuticular and staples) by random selection. Assessment parameters being skin closure time; induration and discharge on day 4 and 8; pain score using visual analogue scale on day 3, day 5 and 7; wound gaping and Patient satisfaction in terms of cosmesis using Likert’s scale after 4-6 weeks. Results: The skin closure time in mattress, subcuticular sutures and staples are found to be 8.891±1.343; 11.390±1.438 and 1.518±0.502 respectively. Pain on day 3, 5 and 7 were: severe pain was maximum seen in staples group (n=21) as compared to 7 patients in subcuticular group and 6 in mattress group. Wound complications were seen least in mattress group. One patient (1.20%) had wound gaping in mattress group, 3 (3.65%) of the patients in subcuticular group and 5 (6.17%) in staples group had wound gaping. Patient dissatisfaction rate was higher in staples group (8.64%) as compared to 6.09% patient in subcuticular group and 4.8% in mattress group. Conclusions: The mattress suturing technique has least wound related complications and most patients satisfaction. Staples are quick in application and subcuticular technique gives a good scar, but is associated with similar complications as staples.